Stress Hyperglycemia, Diabetes Mellitus and COVID-19 Infection: Risk Factors, Clinical Outcomes and Post-Discharge Implications - Gerganova, Antonina; Assyov, Yavor; Kamenov, Zdravko (Frontiers in Clinical Diabetes and Healthcare, 2022)
The novel severe acute respiratory distress syndrome-coronavirus 2 (SARS-CoV-2) has caused one of the most substantial pandemics that has affected humanity in the last century. At the time of the preparation of this review, it has caused the death of around 5 million people around the globe. There is ample evidence linking higher mortality risk rates from Coronavirus disease-19 (COVID-19) with male gender, advancing age and comorbidities, such as obesity, arterial hypertension, cardiovascular disease, chronic obstructive pulmonary disease, diabetes mellitus, and cancer. Hyperglycemia has been found to be accompanying COVID-19 not only in individuals with overt diabetes. Many authors claim that blood glucose levels should also be monitored in non-diabetic patients; moreover, it has been confirmed that hyperglycemia worsens the prognosis even without pre-existing diabetes. The pathophysiological mechanisms behind this phenomenon are complex, remain controversial, and are poorly understood. Hyperglycemia in the setting of COVID-19 could be a consequence of deterioration in pre-existing diabetes, new-onset diabetes, stress-induced or iatrogenic due to substantial usage of corticosteroids within the context of a severe COVID-19 infection. It is also plausible that it might be a result of adipose tissue dysfunction and insulin resistance. Last but not least, SARS-CoV-2 is also claimed to trigger sporadically direct β-cell destruction and β-cell autoimmunity. Pending further validations with longitudinal data are needed to legitimize COVID-19 as a potential risk factor for the development of diabetes. Hereby, we present an emphasized critical review of the available clinical data in an attempt to unravel the complex mechanisms behind hyperglycemia in COVID-19 infection. The secondary endpoint was to evaluate the bidirectional relationship between COVID-19 and diabetes mellitus. As the worldwide pandemic is still expanding, demand for answering these questions is arising. It will be of immense help for the management of COVID-19 patients, as well as for the implementation of post-discharge policies for patients with a high risk of developing diabetes.